2015
DOI: 10.1016/j.ejfs.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the thumbprint ridge density in a central Indian population

Abstract: Background: Identification of sex plays a vital role in forensic and medico legal investigations. Fingerprints are considered to be the most precise and reliable indicators for personal and gender identification. Objectives: The objective of this study was to determine any significant difference in the thumbprint ridge density of males and females in a central Indian (Marathi) population to enable the determination of gender. Methods and materials: The study was conducted on 200 subjects (100 males and 100 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…Compared to other population (Cummins, 1941), the ridges observed in the current study were thicker. This is in keeping with the previous studies on the ridge density, where Africans, Hausa ethnic group (Adamu et al, 2016) and Sudanese (Ahmed and Osman, 2016) were observed to have lower ridge density compared to Argentinians, Spaniards and central Indians (Gutie´rrez-Redomero et al, 2008;Kapoor and Badiye, 2015;Rivalderia et al, 2016). This led to the suggestion that lower ridge density was more an indicator of African descent (Adamu et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Compared to other population (Cummins, 1941), the ridges observed in the current study were thicker. This is in keeping with the previous studies on the ridge density, where Africans, Hausa ethnic group (Adamu et al, 2016) and Sudanese (Ahmed and Osman, 2016) were observed to have lower ridge density compared to Argentinians, Spaniards and central Indians (Gutie´rrez-Redomero et al, 2008;Kapoor and Badiye, 2015;Rivalderia et al, 2016). This led to the suggestion that lower ridge density was more an indicator of African descent (Adamu et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…In addition to the use of fingerprints within the forensic community for many decades, their persistence and biological uniqueness allow them to be used for identification of victims of mass disasters when traditional identification becomes difficult or other anthropometric methods are not feasible (Krishan et al, 2013;Rivalderia et al, 2016). Previous studies have dealt with features such as minutiae (Stoney and Thornton, 1986;Gutierrez-Redomero et al, 2007;Reinart, 2014;Adamu et al, 2017), ridge density (Gutierrez-Redomero et al, 2013;Kapoor and Badiye, 2015;Adamu et al, 2016;Rivalderia et al, 2016), epidermal ridge width (Cseplák, 1982;Kamp et al, 1999;Králík et al, 2002) in connection with biological profile such as gender and age of an individual. The studies conducted by Adamu et al(2016) which predicted sex among same population using ridge density and thickness probably is the only study reported among Hausa ethnic group of Kano state, Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…This is due in part to the number and distribution of sweat ducts, with men having more of them, as well as to hormone metabolism . Moreover, according to Kapoor and Badiye , the friction ridge impression in men's fingerprints is usually as much as 10% wider. Examination of the questionnaires filled out in our research showed that the majority of women participating in the study, unlike the men, used emollients after washing their hands, which may explain the results.…”
Section: Resultsmentioning
confidence: 99%
“…2 Fingerprints or friction ridges are the prime and infallible means of identification in forensic investigations and trials. 3 Unless a person is involved in an accident affecting their hands, the fingerprints remain unchanged during life time (except for growing in the size with age, proportionately to the growth of the individual). Even after almost over a century of existence, no two fingers have ever been found to possess identical ridge characteristics (minutiae).…”
Section: Introductionmentioning
confidence: 98%